Hepatorenal protective effect of ocimum sanctum in chickens toxicated by gentamicin - A. M. Abdul Ghaffar, Hadeer; A. A.Elkomy, Ashraf; A.H. Farag, Enas (International Journal of Pharmacology and Toxicology, 2021)
Background: ocimum sanctum (Tulsi) â€œQueen of herbsâ€ is considered as sacred and medicinal plant in a lot of countries around the world especially India. Therefore this study was carried out to investigate the heptorenal protective effect of ocimum sanctum aqueous extract against gentamicin induced hepatorenal toxicity in chickens.Materials and Methods: A total 100, one-day old unsexed broiler chicks of a commercial breed (Cobb breed) were used in this study, the chickens were subjected to different treatments blood and tissue samples were collected at 5th week of age post administration, biochemical and histopathological examinations were utilized to investigate protective effect of ocimum sanctum aqueous extract on liver and kidney.Results: gentamicin recorded significant (P<0.05)increase in serum level of aspartate aminotransferase (AST), alanine aminotransferase (ALT), uric acid and creatinine levels when compared with control group, the administration of ocimum sanctum aqueous extract with gentamicin ameliorate their toxic effect, the group treated with ocimum sanctum aqueous extract only similar to control, while gentamicin induce significant (P<0.05)decrease in serum albumin, total protein and globulin levels when compared with control group, ocimum sanctum aqueous extract with gentamicin restore their toxic effect. The group treated with ocimum sanctum aqueous extract only as control. Gentamicin induce histopathological alterations in liver and kidney tissues by comparison with control group and ocimum sanctum aqueous extract treated group as control, while the administration of ocimum sanctum aqueous extract with gentamicin showing improvement in histopathological lesion compared with toxic effect induced by gentamicin.Conclusions: The hepatotoxicity and nephrotoxicity induced by gentamicin were ameliorated by aqueous extract of ocimum sanctum especially at dose of 2ml/liter in drinking water for 12 days.Â Â Â